Analisis Kesalahan Mahasiswa Dalam Menyelesaikan Soal Cerita Ekonomi Perkebunan di Prodi Sains Perkopian Universitas Pat Petulai - Tanti Novita; Novriza Wahyu Ardiansyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to analyze the types of errors and factors that cause students' errors in solving plantation economics story questions. This research is a qualitative and quantitative descriptive research. The subjects in this research were students in the second semester of the Pat Petulai University Coffee Science Study Program for the 2023/2024 academic year, totaling 18 students. The instruments and data collection techniques used in this research were test sheets, interviews and questionnaires. The results of the research show that the types of errors made by students are (1) conceptual errors by 96.55% of students (2) calculation errors by 86.20% of students, (3) errors in reading questions by 89.65% of students, (4) strategic errors amounted to 79.31% of students (5) data usage errors amounted to 65.51% of students. Factors causing errors include poor understanding of concepts, weak mathematics skills, affective factors, less effective teaching methods.